Peningkatan Literasi Numerasi Siswa SMA Melalui Pembinaan AKM untuk Mencapai Sekolah Berkualitas - Masnia, Masnia; Saputri, Veni; Kamsurya, Rizal; Tuhu, Dewi Masito Setyo (Penerbit Goodwood, 2025)
The purpose of this Community Service (PKM) activity is to improve the numeracy ability of Tadika Pertiwi Senior High School students through the coaching of Minimum Competency Assessment (AKM), to create a quality school. The methodology used in this activity is Blended Learning which combines material delivery and AKM question practice through Google Classroom and Google Meet. This activity took place at Tadika Pertiwi High School and involved lecturers and students from the mathematics education study program at Media Nusantara Citra University. The results of this PKM activity show that students have a better understanding of AKM questions, are better prepared to take AKM at school, and there is a significant improvement in student numeracy results. An evaluation was conducted through assignments and students' AKM results. Although there were obstacles such as network problems and conflicting student schedules, this activity was still successful thanks to the effective collaboration between the school and the PKM team. In conclusion, AKM coaching improves students' numeracy ability and creates a more interactive and collaborative learning environment. Thus, SMA Tadika Pertiwi can continue to improve the quality of its education and produce excellent students who are ready to face various academic challenges in the future